In Vivo Bioequivalence Study of Drug: An Analysis of Related Regulations in Current Pharmaceutical Legislation in Vietnam - Quoc Hung, Tang; Thanh Hai, Nguyen; Bich Ngoc, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1DO - 10.25073/2588-1132/vnumps.4474, 2023)
Abstract : Implementation of in vivo bioequivalence study is a growing trend in the pharmaceutical industry in Vietnam and over the world. These studies are required in order to demonstrate whether a generic drug is a bioequivalence to an innovator’s drug or to an original brand name drug. At present, there are 26 active ingredients that have to provide in vivo bioequivalence study report for drug registration in Vietnam. In the next few years, this number will gradually increase. Therefore, the government should introduce promotion, development, and preferential policies for enterprises to invest in these ingredients. This paper aims to provide general guidelines on regulations of in vivo bioequivalence studies for pharmaceutical enterprises in Vietnam and support the initial implementation of these studies in practice. Keywords : Bioequivalence, BABE, BE, Regulations.